Baseline CD4 T cell level predicts recovery rate after initiation of art In HIV Infected Nigerians (2016)
The most characteristic immunologic disorder in HIV infection is the progressive loss of CD4 Tlymphocytes, thus, it remains the most important and commonly used marker for monitoring ofimmune status of HIV-infected individuals. This study monitored CD4 T lymphocyte cell dynamics among HIV patients on ART, and consequently defined an optimal baseline level required for enhanced ARV treatment. Ninety-eight (M = 33; F = 65) out of 106 consenting HIV-infected ARV-naïve patients enrolled and monitored for 24 months were considered in the analysis. The patients were classified into four groups based on baseline CD4 T lymphocyte cell levels, and specific parameters were evaluated at interval. Median CD4 T lymphocyte increased from 114 (Range: 6–330) at baseline to highest 357 (Range: 15–1036) cells/μL at 18 months of therapy. Fifty (51.0%), 58(59.2%), 75(76.5%), 69(70.4%), 63(64.3%), and 69(70.4%) doubled their preceding CD4 levels during the 3rd, 6th, 9th, 12th, 18th, and 24th months of ART, respectively. Maximum 337, 302, 360, and 475 cells/μL of blood were attained by groups commenced on ART with baseline CD4 ≤ 50, 51–100, 101–200, and 201–350 cells/μL of blood, respectively. The results show that higher baseline CD4 T lymphocyte cell level correlates with enhanced restoration,and plateau after commencement of ART.